THE EFFECTIVENESS OF SQ4R COOPERATIVE LEARNING METHOD ON READING LEARNING FOR EFL STUDENTS - Maulizan ZA; Khatmi Khatmi (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2020)
The aims of study is to determine the effectiveness of the SQ4R method in learning to read comprehension at SMAN 1 Darul Imarah. This study used a pre experimental design with a One Group Pretest Posttest Design design. The subjects of this study were students of class X (IPS 1) at SMAN 1 Darul Imarah. Data were analyzed using Effect Size. The results showed that the pretest mean score before using the SQ4R method was 62.59 and the posttest mean score was 82.76. Based on the calculation of Effect Size, where the Effect Size value between the pretest and posttest is 1.28 with a large category, meaning that there is the effectiveness of the application of the SQ4R method on student learning outcomes in learning reading comprehension in class X (IPS 1) SMA Negeri 1 Darul Imarah